High-temperature resistance-stable cable shielding material, preparation method and application thereof

CN119798835BActive Publication Date: 2026-10-23WANHUA CHEM GRP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510001498.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2026-10-23
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

但是液态金属颗粒的为圆形填料,填料间的搭接效应不明显

Benefits of technology

[0054](1)高温导电稳定性:铜纳米线具有优异的导电性能,能够搭接炭黑颗粒,能够在高温环境时树脂基体膨胀后,仍然产生搭接作用,保持较低的电阻,确保电缆的长期可靠运行。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225364210000071
    Figure BDA0005225364210000071
  • Figure BDA0005225364210000081
    Figure BDA0005225364210000081
Patent Text Reader

Abstract

The present application relates to a kind of high temperature resistance stable cable shielding material and its preparation method and application, the raw material mass percentage composition of the high temperature resistance stable cable shielding material includes: matrix resin 45.0-75.0%, carbon black 10.0-35.0%, copper nanowire 0.5-5.0%, antioxidant 0.1-1.0%, crosslinking agent 0.5-2.0%.By using the way of carbon black and copper nanowire, the conductivity of shielding material is significantly improved, especially in high temperature environment, after the expansion of resin matrix, copper nanowire can lap carbon black, so that the shielding material can still maintain the conductivity in high temperature. Copper nanowire is oriented along the extrusion direction during the extrusion into cable, so it can strengthen the uniformization of electric field distribution and improve the durability of cable. At the same time, the introduction of copper nanowire effectively reduces the amount of carbon black, improves the smoothness of the material, and reduces the defect rate during cable manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor shielding materials for high-voltage cables, specifically to a high-temperature resistance-stable cable shielding material, its preparation method, and its application. Background Technology

[0002] In modern society, with the rapid development of the power industry, high-voltage cables are widely used in power transmission systems, playing a crucial role, especially in energy, industry, and transportation. The performance of high-voltage cables directly affects the safety and stability of power systems, thus placing increasingly stringent requirements on their materials. Semi-conductive shielding material is a vital component of high-voltage cables. It prevents electric field concentration caused by conductor burrs or inhomogeneities, promotes uniform electric field distribution, reduces the electric field strength between the conductor and insulation layer, prevents partial discharge, and thus protects the insulation layer from damage, extending the cable's service life. The shielding layer also helps reduce electrochemical corrosion caused by charge accumulation between the conductor and shielding layer during operation, improving cable reliability.

[0003] In certain special environmental conditions, such as high-temperature environments, the resistance of ordinary cable shielding materials increases, and their shielding performance decreases, making it difficult to maintain their original performance at high temperatures. Therefore, developing high-voltage cable shielding materials suitable for high-temperature conditions is particularly important. Shielding materials suitable for high-temperature conditions not only need to possess excellent thermal stability but also good electrical properties, mechanical strength, and processability to adapt to diverse application scenarios. Meanwhile, as the operating voltage of high-voltage transmission lines gradually increases, the requirements for the voltage withstand capability and anti-aging performance of cable materials are also constantly strengthening. In summary, developing cable shielding materials that can effectively operate under high temperature and high pressure conditions has become an urgent technical requirement to ensure the stable operation of high-voltage cables in harsh environments.

[0004] In the prior art, Chinese patent CN 105367918 A uses EPDM rubber with high ethylene content and low third monomer content as the matrix to make the shielding material have good processability, thermal stability and non-peelability. It uses diphenylamine and p-phenylenediamine antioxidants to prepare a halogen-free, high-temperature resistant conductor shielding material with good processability, thermal stability, mechanical properties and electrical properties, and still has excellent semi-conductive properties at high temperatures.

[0005] Chinese patent CN 111303526 A modifies EVA resin with low melt index polyethylene by crosslinking, introduces conductive carbon black and multilayer graphene. The multilayer graphene itself has a continuous layered structure, which is conducive to forming a uniform planar electric field inside the shielding material. Under the action of multifunctional silane coupling agent, a uniform and stable molecular structure is formed between each resin, conductive carbon black and multilayer graphene, thus preparing a cable semiconductive shielding material that can operate stably in high temperature environment.

[0006] Chinese patent CN 105131413 A uses an internal mixer to initially mix EVA, conductive carbon black, POE, antioxidants, and plasticizers, and then adds modifying agents and p-hydroxybenzenesulfonic acid for a second mixing, which improves the strength and toughness of the shielding material in low-temperature environments and its high-temperature resistance.

[0007] While these methods can improve the resistivity stability of shielding materials at high temperatures to some extent, the amount of carbon black used is still relatively high, and the number of protrusions in the shielding material is also relatively large, leaving room for improvement in long-term stability at high temperatures. Chinese patent CN115838511A introduces liquid metal into semi-conductive shielding materials, reducing the amount of conductive carbon black used, suppressing the high-temperature resistivity of the semi-conductive shielding material, and lowering the PTC coefficient. However, the liquid metal particles are spherical fillers, and the overlap effect between fillers is not significant.

[0008] Therefore, it is necessary to reduce the amount of carbon black used, improve the electrical resistance stability of the shielding material at high temperatures, and at the same time maintain a good ability to suppress space charge at high temperatures, so as to solve the problems of large carbon black usage and poor long-term operational stability at high temperatures in existing technologies. Summary of the Invention

[0009] To address the aforementioned problems in existing technologies, this invention aims to provide a cable shielding material with high-temperature resistance stability. This is achieved by using copper nanowires in combination with carbon black to improve the conductivity of the shielding material at high temperatures. Copper nanowires are one-dimensional conductive materials with a high aspect ratio, capable of overlapping with carbon black. At high temperatures, the resin matrix expands, and the high aspect ratio of the copper nanowires ensures the overlap of the carbon black, thus improving conductivity at high temperatures. Furthermore, this invention achieves a more uniform electric field distribution through the orientation effect of the copper nanowires during extrusion, thereby improving the operational stability of the cable at high temperatures.

[0010] To achieve the above-mentioned objectives, the specific technical solution adopted by the present invention is as follows:

[0011] On the one hand, the present invention provides a cable shielding material with high temperature resistance stability, the raw materials of which include matrix resin, carbon black, copper nanowires, antioxidants and crosslinking agents.

[0012] In one embodiment, the raw material mass percentage composition of the high-temperature resistance-stability cable shielding material includes:

[0013] The matrix resin is 45.0-77.0%, for example, 45.0%, 50.0%, 55.0%, 60.0%, 65.0%, 70.0%, 75.0%, etc., preferably 50.0-65.0%;

[0014] Carbon black content is 10.0-35.0%, such as 10.0%, 15.0%, 20.0%, 25.0%, 30.0%, 35.0%, etc., preferably 15.0-25.0%;

[0015] The copper nanowires comprise 0.5-5.0%, such as 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc., preferably 1.0-3.0%.

[0016] Antioxidant 0.1-1.0%, such as 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.0%, etc., preferably 0.2-0.5%;

[0017] The crosslinking agent is 0.5-2.0%, such as 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc., preferably 1.0-2.0%.

[0018] In one embodiment, the aspect ratio of the copper nanowire is 20-100, such as 20, 30, 40, 50, 60, 70, 80, 90, 100, etc., preferably 30-60;

[0019] Preferably, the copper nanowires have a length of 1-15 μm, such as 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, 13 μm, etc.

[0020] In one embodiment, the density of the matrix resin is 0.91-0.94 g / cm³. 3 The preferred concentration is 0.92-0.93 g / cm³. 3 ;

[0021] Preferably, the matrix resin is selected from one or more of ethylene-ethyl acrylate copolymer (EEA), ethylene-acrylic acid copolymer (EAA), ethylene-butyl acrylate copolymer (EBA), ethylene and methyl acrylate copolymer (EMA), or ethylene-vinyl acetate copolymer (EVA), more preferably one or more of EBA and EEA;

[0022] Specifically, the matrix resin is selected from any one or a combination of at least two of Dow 3427, Dow 3717, and Repsol E1770, preferably Dow 3427.

[0023] In one embodiment, the carbon black is selected from highly conductive carbon black, specifically from one or more of Ketjen Black ECP-600JD, ECP-300JD, and Cabot VXC500, preferably Ketjen Black ECP-600JD.

[0024] The high-temperature resistance-stability cable shielding material of the present invention also contains crosslinking agents and antioxidants, which are commonly used additives in the field and have no special requirements. They can be selected in the conventional way in the field.

[0025] In one embodiment, the crosslinking agent is selected from one or more of dicumyl peroxide, benzoyl peroxide, and di-tert-butyl peroxide, preferably one or more of dicumyl peroxide and di-tert-butyl peroxide;

[0026] The antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant DSTP and antioxidant MB, preferably one or more of antioxidant 300 and antioxidant MB.

[0027] On the other hand, the present invention also provides a method for preparing the above-mentioned high-temperature resistance stable cable shielding material, the preparation method comprising the following steps:

[0028] S1: The matrix resin, carbon black, antioxidant, and copper nanowires are added to a reciprocating single-screw extruder for compounding and extrusion.

[0029] S2: After mixing with a crosslinking agent and performing a post-absorption operation, the high-temperature resistance-stable cable shielding granules are obtained.

[0030] In one embodiment, the temperature of the compounding extrusion in step S1) is 100-180°C, preferably 120-160°C, and the rotation speed is 5-70 rpm, preferably 20-50 rpm; the copper nanowires are oriented along the extrusion direction to form a shielding material structure with a homogenized electric field.

[0031] In one embodiment, the temperature of the post-absorption operation in step S2) is 40-100°C, preferably 65-70°C, and the time is 0.5-16h, preferably 1-8h.

[0032] This invention introduces copper nanowires into cable shielding materials. When the resin matrix expands at high temperatures, the aspect ratio structure of the copper nanowires can overlap with carbon black particles, suppressing the increase in resistivity. Simultaneously, during the extrusion process of the cable material, the silver nanowires can orient themselves along the extrusion direction, achieving a more uniform electric field distribution and improving the cable's operational stability at high temperatures.

[0033] Furthermore, the present invention also provides the application of the above-mentioned high-temperature resistance stable cable shielding material.

[0034] One specific application is in the preparation of cables with high-temperature resistance stability, which can operate stably at high temperatures. The specific method is to use the high-temperature resistance stable cable shielding material described in this invention as the inner shielding layer and the outer shielding layer, and to perform three-layer co-extrusion extrusion with the insulating material to form a shielding layer-insulation layer-shielding layer composition, thereby obtaining the cable.

[0035] The method for preparing the above-mentioned shielding-insulation-shielding layer composition by extruding cable shielding material and insulation material is an existing process. The related operations, process conditions, and equipment used can all be selected using conventional methods in the art, and there are no particular limitations. Those skilled in the art can optimize the process based on existing technology and known processes, according to actual needs. Specifically, for example, the conditions listed in the following embodiments of the present invention can be used:

[0036] Preferably, the mass ratio of the high-temperature resistance-stability cable shielding material to the insulation material is 1:1-4, wherein the mass ratio of the inner shielding layer to the outer shielding layer is preferably 1:0.5-2.

[0037] Preferably, the insulating material is selected from one or more of Dow HFDB 4201SC, Borealis LS4201H, and LE4244S, with Dow HFDB 4201SC being the most preferred.

[0038] Preferably, during the co-extrusion process to form the shielding layer-insulation layer-shielding layer composition, the extrusion temperature of the shielding material is 90-120℃, the rotation speed is 5-8 rpm, the temperature is 110-130℃, and the rotation speed is 3-7 rpm.

[0039] The insulating cable shielding material of the present invention has an electric field enhancement coefficient FEF of 1.2 or less, preferably 1.0-1.2, as defined by Formula 1 below;

[0040] FEF=(B / A)×100 (1)

[0041] In Formula 1, A represents the electric field applied to the shielding layer-insulating layer-shielding layer composition, specifically the DC electric field applied to the electrodes respectively connected to the mutually facing surfaces of the shielding layer-insulating layer-shielding layer composition, and is 50 kV / mm;

[0042] B indicates the maximum increase in electric field in the shielding-insulation-shielding composition, wherein the thickness of the insulating layer in the shielding-insulation-shielding composition is 120 μm. Specifically, the maximum increase in electric field in the shielding-insulation-shielding composition refers to the maximum value of the electric field increase during the application of a 50 kV / mm DC electric field to the shielding-insulation-shielding composition for 1 hour.

[0043] The copper nanowires involved in the high-temperature resistance-stable cable shielding material of the present invention have been addressed in the prior art. They can be ordinary commercially available products or prepared by conventional methods in the art using existing processes. The operation and process conditions of the present invention, as well as the apparatus used, can all be carried out by corresponding conventional selections in the art, and there are no particular restrictions.

[0044] For example, in one embodiment, the method for preparing the copper nanowires includes the following steps:

[0045] The copper salt, reducing agent, and solvent are mixed, ultrasonically dispersed, and then heated to react. After separation, washing with water, and drying, the copper nanowires are obtained.

[0046] The copper salt is selected from one or more of copper nitrate, copper sulfate, and copper chloride, preferably one or more of copper nitrate and copper sulfate;

[0047] The reducing agent is selected from one or more of sodium borohydride, hydrazine hydrate, and ascorbic acid, preferably one or more of ascorbic acid and sodium borohydride;

[0048] The solvent is selected from one or more of ethanol, methanol, acetone, and tetrahydrofuran, preferably one or more of ethanol and acetone.

[0049] The mass ratio of the copper salt to the reducing agent is 0.2-5, preferably 0.6-1.7;

[0050] The concentration of the copper salt in the solvent is 0.01-1 mol / L, preferably 0.2-0.7 mol / L.

[0051] The heating reaction temperature is 60-120℃, and the reaction time is 1-6h; preferably, the heating temperature is 80℃ and the reaction time is 2h.

[0052] The above methods also include conventional operations in the fields of ultrasonic dispersion, separation, water washing, and drying, which are not specifically required in this invention.

[0053] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0054] (1) High temperature conductivity stability: Copper nanowires have excellent conductivity and can overlap carbon black particles. Even after the resin matrix expands in a high temperature environment, they can still overlap, maintain low resistance, and ensure the long-term reliable operation of the cable.

[0055] (2) Homogenized electric field: During the extrusion process, the material is oriented along the extrusion direction, thereby forming a uniform shielding layer. When the cable is running, a uniform electric field distribution is formed, which significantly suppresses the accumulation of space charge and improves the service life of the cable.

[0056] (3) Reduce carbon black usage: The introduction of copper nanowires improves the conductivity of the material, thereby reducing the amount of carbon black used and improving the smoothness of the shielding material.

[0057] (3) Cost-effectiveness: Compared with the use of conductive materials such as graphene alone, the synergistic effect of copper nanowires and carbon black not only improves conductivity but also effectively controls material costs. The prepared shielding material can meet the requirements of high-voltage cables operating at high temperatures for extended periods without breakdown. Detailed Implementation

[0058] The present invention will be further described below with reference to the embodiments, but the scope of protection of the present invention is not limited to the embodiments, but should also include any other known modifications within the scope of the claims of the present invention.

[0059] Unless otherwise specified, the reagents, materials and instruments used in the following examples are all conventional reagents, materials and instruments in the art, and can be obtained commercially.

[0060] The sources of the main raw materials used in the various embodiments and comparative examples of this invention are as follows:

[0061] EBA: Dow 3427;

[0062] Crosslinking agent: dicumyl peroxide (DCP), Aladdin Company, purity 99.0%;

[0063] Antioxidant 300: JYANOX 300 from Jiyi Chemical, 99.0% purity;

[0064] Antioxidant MB, Lanxess, 95% purity;

[0065] Carbon black: Ketjen Black ECP 600-JD;

[0066] Copper nitrate: Aladdin Company, purity 99.0%;

[0067] Ascorbic acid: Aladdin Company, purity 99.0%;

[0068] Cable insulation material: Dow HFDB 4201SC.

[0069] Preparation Example 1

[0070] Preparation of copper nanowires 1-3:

[0071] Sample 1: 50 g (0.27 mol) of copper nitrate was added to 500 mL of ethanol, ultrasonically dispersed, and then 30 g of ascorbic acid was added. The mixture was stirred at 80 °C for 2 hours. After the reaction was completed, the copper nanowires were separated by centrifugation, washed with water, and vacuum dried at 60 °C to obtain copper nanowire 1 with an aspect ratio of 50 and a length of 10 μm.

[0072] Sample 2: 50g of copper nitrate was added to 1000mL of acetone solvent, ultrasonically dispersed, and then 10g of sodium borohydride reducing agent was added. The mixture was stirred at 60℃ for 1 hour. After the reaction was completed, the copper nanowires were separated by centrifugation, washed with water, and vacuum dried at 60℃ to obtain copper nanowire 2 with an aspect ratio of 40 and a length of 5μm.

[0073] Sample 3: 50g of copper sulfate was added to 500mL of solvent ethanol, ultrasonically dispersed, and then 20g of reducing agent hydrazine hydrate was added. The mixture was stirred at 70℃ for 4 hours. After the reaction was completed, the copper nanowires were separated by centrifugation, washed with water, and vacuum dried at 60℃ to obtain copper nanowire 3 with an aspect ratio of 30 and a length of 3μm.

[0074] Example 1

[0075] Preparation of cable shielding material with high-temperature resistance stability:

[0076] The raw material composition by weight percentage is 71.2% EBA matrix resin, 25% Ketjen Black ECP-600JD carbon black, 2% copper nanowires, 0.3% antioxidant 300, and 1.5% crosslinking agent DCP;

[0077] 71.2% EBA matrix resin, 25% Ketjen Black ECP-600JD carbon black, 2% copper nanowires, and 0.3% antioxidant 300 were compounded and extruded in an extruder at a compounding temperature of 120-160℃ and an extrusion speed of 30 rpm. During extrusion, the copper nanowires and carbon black oriented along the extrusion direction, forming a uniform conductive network. After compounding, 1.5% crosslinking agent DCP was added for further mixing and absorption. The absorption temperature was 70℃ for 2 hours. After cooling, the finished cable shielding material granules with high-temperature resistance stability were obtained.

[0078] A certain amount of high-temperature resistivity stable cable shielding material granules and Dow HFDB 4201SC insulation material were extruded at a mass ratio of 1:4 to form a shielding layer-insulation layer-shielding layer composition (where the mass ratio of the inner shielding layer to the outer shielding layer was 1:1). The extrusion speed was 6 rpm, the insulation material temperature was 120℃, and the extrusion speed was 5 rpm to obtain the cable. The cable was then subjected to voltage and space charge tests.

[0079] The prepared materials were tested for tensile properties, aging properties, volume resistivity at room temperature and high temperature, and surface protrusions.

[0080] The performance test results are shown in Table 1.

[0081] Example 2

[0082] Preparation of cable shielding material with high-temperature resistance stability:

[0083] The raw material composition by weight percentage is 65.2% EBA matrix resin, 30% Ketjen Black ECP-600JD carbon black, 3% copper nanowires 2, 0.3% antioxidant 300, and 1.5% crosslinking agent DCP;

[0084] 65.2% EBA matrix resin, 30% Ketjen Black ECP-600JD carbon black, 3% copper nanowires, and 0.3% antioxidant 300 were compounded and extruded in an extruder at a compounding temperature of 120-160℃ and an extrusion speed of 20 pm. During extrusion, the copper nanowires and carbon black oriented along the extrusion direction, forming a uniform conductive network. After compounding, 1.5% crosslinking agent DCP was added for post-absorption at a temperature of 70℃. After cooling, the resulting cable shielding material granules exhibiting high-temperature resistance stability were obtained.

[0085] A certain amount of sample was taken and extruded into cables according to the method in Example 1. The resulting cables were then subjected to voltage and space charge tests.

[0086] The prepared materials were tested for tensile properties, aging properties, volume resistivity at room temperature and high temperature, and surface protrusions.

[0087] Example 3

[0088] Preparation of cable shielding material with high-temperature resistance stability:

[0089] The raw material composition by weight percentage is 59.5% EEA matrix resin, 35% Ketjen Black ECP-600JD carbon black, 4% copper nanowires 3, 0.2% antioxidant 300, and 1.3% crosslinking agent DCP;

[0090] 59.5% EEA matrix resin, 35% Ketjen Black ECP-600JD carbon black, 4% copper nanowires, and 0.2% antioxidant 300 were compounded and extruded in an extruder at a compounding temperature of 120-160℃ and an extrusion speed of 50 rpm. During extrusion, the copper nanowires and carbon black oriented along the extrusion direction, forming a uniform conductive network. After compounding, 1.3% crosslinking agent DCP was added for post-absorption at a temperature of 70℃. After cooling, the resulting cable shielding material granules exhibiting high-temperature resistance stability were obtained.

[0091] A certain amount of sample was taken and extruded into cables according to the method in Example 1. The resulting cables were then subjected to voltage and space charge tests.

[0092] The prepared materials were tested for tensile properties, aging properties, volume resistivity at room temperature and high temperature, and surface protrusions.

[0093] Comparative Example 1

[0094] The method of Example 1 was followed, except that copper nanowires 1 were replaced with copper powder of equal mass (particle size 5-7 μm), while other operations and conditions remained unchanged. The results are shown in Table 1.

[0095] Comparative Example 2

[0096] The method of Example 2 was followed, except that copper nanowires 2 were not added, while other operations and conditions remained unchanged. The results are shown in Table 1.

[0097] The materials prepared in the examples and comparative examples were tested for tensile properties, aging properties, thermal elongation, volume resistivity, surface protrusions, and field strength enhancement factor (FEF). The specific test results are shown in Table 1.

[0098] Voltage testing shall be conducted in accordance with GB / T 18890-2015;

[0099] Space charge testing shall be performed in accordance with JBT 12927-2016;

[0100] For other specific testing methods, please refer to QGDW 11883.2—2018.

[0101] Table 1. Performance comparison data of samples from the examples and comparative examples.

[0102]

[0103]

[0104] Comparing the data in the table above, it can be seen that the embodiments are significantly superior to the comparative examples in terms of semiconductor resistivity, mechanical properties, and surface protrusion properties at both room temperature (23℃) and high temperature (90℃). The semiconductor resistivity data shows that the conductivity of the material is greatly improved after adding an appropriate proportion of copper nanowires, and the resistance remains stable even at high temperatures. The shielding material with added copper nanowires exhibits better interfacial interaction with the insulating material, resulting in significantly better withstand voltage tests and field strength enhancement coefficients after cabling. This indicates that the shielding material with added copper nanowires has significant advantages in reducing space charge. In particular, Embodiment 3, due to the addition of a large amount of copper nanowires, exhibits the best conductivity, withstand voltage tests after cabling, and field strength enhancement coefficient. Simultaneously, the addition of copper nanowires improves the material's conductivity, and its two-dimensional network structure can interact with carbon black particles, maintaining a low resistance while reducing the protrusion content.

[0105] The above embodiments are only used to describe preferred embodiments of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that various modifications and improvements made to the technical solutions of the present invention by means of modifications or equivalent substitutions should fall within the scope of protection defined by the claims of the present invention.

Claims

1. A cable shielding material with high-temperature resistance stability, characterized in that, The raw materials include matrix resin, carbon black, copper nanowires, antioxidants, and crosslinking agents; The copper nanowires have an aspect ratio of 20-100 and a length of 1-15 μm; The raw material mass percentage composition of the cable shielding material with high temperature resistance stability includes: Matrix resin 45.0-77.0%; Carbon black 10.0-35.0%; Copper nanowires 0.5-5.0%; Antioxidant 0.1-1.0%; Crosslinking agent 0.5-2.0%; The sum of the mass percentages of all raw materials is 100%.

2. The cable shielding material with high-temperature resistance stability according to claim 1, characterized in that, The raw material mass percentage composition of the cable shielding material with high temperature resistance stability includes: Matrix resin 50.0-65.0%; Carbon black 15.0-25.0%; Copper nanowires 1.0-3.0%; Antioxidant 0.2-0.5%; Crosslinking agent 1.0-2.0%; The sum of the mass percentages of all raw materials is 100%.

3. The cable shielding material with high-temperature resistance stability according to claim 1, characterized in that, The aspect ratio of the copper nanowires is 30-60.

4. The cable shielding material with high-temperature resistance stability according to claim 1, characterized in that, The density of the matrix resin is 0.91-0.94 g / cm³. 3 ; and / or The carbon black is selected from highly conductive carbon black; and / or The crosslinking agent is selected from one or more of dicumyl peroxide (DCP), benzoyl peroxide (BPO), and di-tert-butyl peroxide; and / or The antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant DSTP, and anti-aging agent MB.

5. The cable shielding material with high-temperature resistance stability according to claim 4, characterized in that, The density of the matrix resin is 0.92-0.93 g / cm³. 3 .

6. The cable shielding material with high-temperature resistance stability according to claim 4, characterized in that, The carbon black is selected from one or more of Ketjen Black ECP-600JD, ECP-300JD, and Cabot VXC500.

7. The cable shielding material with high-temperature resistance stability according to claim 4, characterized in that, The matrix resin is selected from one or more of ethylene-ethyl acrylate copolymer (EEA), ethylene-acrylic acid copolymer (EAA), ethylene-butyl acrylate copolymer (EBA), ethylene and methyl acrylate copolymer (EMA), or ethylene-vinyl acetate copolymer (EVA).

8. The cable shielding material with high-temperature resistance stability according to claim 4, characterized in that, The matrix resin is selected from any one or a combination of at least two of Dow 3427, Dow 3717, and Repsol E1770.

9. A method for preparing a cable shielding material with high-temperature resistance stability as described in any one of claims 1-8, characterized in that, Includes the following steps: S1: The matrix resin, carbon black, antioxidant, and copper nanowires are added to a reciprocating single-screw extruder for compounding and extrusion. S2: After mixing with a crosslinking agent and performing a post-absorption operation, the high-temperature resistance-stable cable shielding granules are obtained.

10. The preparation method according to claim 9, characterized in that, Step S1) The temperature of the compounding extrusion is 100-180℃, and the rotation speed is 5-70 rpm; and / or The temperature of the post-absorption operation in step S2) is 40-100℃, and the time is 0.5-16h.

11. The preparation method according to claim 10, characterized in that, In step S1), the temperature of the compounding extrusion is 120-160℃ and the rotation speed is 20-50rpm.

12. The preparation method according to claim 10, characterized in that, The temperature for the post-absorption operation in step S2) is 65-70℃, and the time is 1-8h.

13. The application of the high-temperature resistance-stable cable shielding material according to any one of claims 1-8 or the high-temperature resistance-stable cable shielding material prepared by the method according to any one of claims 9-12 in cable manufacturing.

14. The application according to claim 13, characterized in that, The specific method involves using the high-temperature resistance-stability cable shielding material as the inner and outer shielding layers, and then co-extruding it with the insulating material to form a shielding layer-insulation layer-shielding layer composition, thereby obtaining the cable.

15. The application according to claim 14, characterized in that, The mass ratio of the cable shielding material to the insulation material for high-temperature resistance stability is 1:1-4, wherein the mass ratio of the inner shielding layer to the outer shielding layer is 1:0.5-2; and / or The insulating material is selected from one or more of Dow HFDB4201SC, Borealis LS4201H, and LE4244S; and / or During the co-extrusion process to form the shielding layer-insulation layer-shielding layer composition, the extrusion temperature of the shielding material is 90-120℃ and the rotation speed is 5-8 rpm.

Citation Information

Patent Citations

  • Semiconductive shielding material for high-strength and high-temperature-resistant silane cross-linked cable and preparing method thereof

    CN105131413A

  • Halogen-free high-temperature-resistant conductor shield material and preparation method thereof

    CN105367918A

  • Multilayer graphene modified semiconductive shielding material and preparation method thereof

    CN111303526A

  • Semi-conductive shielding material for high-voltage cable and preparation method of semi-conductive shielding material

    CN115838511A

  • Copper nanowire conductive adhesive and preparation method thereof

    CN103911089A